Pelatihan Keterampilan Desain Grafis bagi Yatim, Piatu, Dhuafa oleh Baznas Bekasi dan Universitas Islam 45 Bekasi - Setyo Supratno; R. Hengki Rahmanto; Sugeng Sugeng; Taufiqur Rokhman (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2025)
This community service activity is a collaboration between BAZNAS Bekasi and Universitas Islam 45 Bekasi which is realized in the form of graphic design training using Adobe Photoshop software. This activity is carried out at the SAINSTECH Laboratory which has modern and adequate facilities to support direct practice. This training targets orphans, half-sixties, and the poor as the main participants, with the main goal of improving their digital skills in the field of graphic design. The training process is guided by experienced lecturers from the Faculty of Engineering, who provide intensive guidance both in theory and practice. The results of this activity show an increase in the participants' ability to operate Adobe Photoshop and produce designs that can be applied to various printing media. In addition, this training is expected to equip participants with relevant skills to face the modern world of work, open up independent business opportunities, and encourage economic independence in the future. This activity is also a real manifestation of the contribution of universities in empowering underprivileged communities.